A Bride by Moonlight - Carlyle,Liz (Harper Collins, 2013)
Passion and secrets simmer behind the elegant façade of Victorian London in A Bride by Moonlight, another deliciously intriguing romance by Liz Carlyle that features the dangerous men of the mysterious St. James Society. Faced with murder charges, Lisette Colburne never imagined aligning herself with Scotland Yard—not with the scandalous life she’s led. But when Commissioner Royden Napier proposes—that in exchange for her freedom—she pretend to be his wife so he can unravel a brutal mystery, she agrees. What neither counts on is their sizzling, undeniable attraction. Sexy and action-packed, Liz Carlyle’s A Bride by Moonlight is a beautiful love story set in Victorian high society with compelling characters and elegant, emotional prose that will appeal to readers of historical romance.